Event-Driven Control for Switched Systems With Quantization and Packet Loss - Jingjing Yan (IEEE, 2020)
In this paper, the problem of designing the quantized feedback controller for a class of continuous-time switched systems with packet loss and event-driven scheme is considered. Two novel event-driven schemes are proposed to reduce the amount of data transmission on the network while ensuring the system stability. Under the assumption of dwell time and maximum consecutive packet loss, we obtain the upper bound of Lyapunov function for both mode-match and mode-mismatch situations. By combining with the mode mismatch interval and the upper bound of Lyapunov function, the practical stability of the closed-loop system is guaranteed. Two numerical examples are given to show the potential of the proposed techniques.